Morfologi Belalang Tongkat (Eurycnema goliath) yang di Pelihara di Tanaman Pucuk Merah (Myrtaceae) di Laboratorium - Puspita Sari, Despi; Irsan, Chandra; Saputra, Eka Bayu; Marlinda, Astry Nurhalifa; Khotimah, Dini Husnul; Salam, Beni; Pratama, Risky Yuda (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Sari, D. P., Irsan, C, Saputra, E. B., Marlinda, A. N., Khotimah, D. H., Salam, B., Pratama, R. Y. (2024). Morphology of stick insect (Eurycnema goliath) reared at red shoots (Myrtaceae) in the labolatory. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 127–134). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Grasshoppers are animals that belong to the insect class. The diversity of grasshoppers can influence the diversity of parasitoids and predators in an ecosystem. Environmental factors are factors that influence the presence of grasshoppers in a habitat. The aimed of this research was to the morphology of stick grasshoppers (Eurycnema goliath) kept on Red Shoot Plants (Myrtaceae) is to observe and describe the morphology of grasshoppers, including body structure, color and size related to their adaptations. This research also aims to assess the interaction of grasshoppers with red shoot plants, such as food preferences and their impact on plant growth. The method used in this research is a survey method by observing and directly measuring the length of the stick grasshopper (E. goliath). The data obtained from these observations are presented in the form of tables and pictures and the results of the observations obtained are described. The results obtained from this research are to understand the life cycle of stick grasshoppers starting from eggs, nymphs, and then imago. The stick mantis eggs are dropped to the ground by the female imago to hatch among the leaves. When entering the nymph phase, the stick grasshopper begins to climb up the stem of the plant that is its habitat. In the first instar nymph phase, the stick grasshopper is whitish brown, then in the second instar the color changes to light brown. The third and fourth instar nymph phases show a change in color to brown, while in the fifth instar, the stick grasshopper is greenish brown. The imago phase is marked by a color change to green. This research shows that keeping stick grasshoppers on plants of the Myrtaceae family helps understand their morphology and type of reproduction. This animal is included in the group that undergoes incomplete metamorphosis.